The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1097/md.0000000000002142
|View full text |Cite
|
Sign up to set email alerts
|

Pleural Empyema and Aortic Aneurysm

Abstract: Pleural empyema (PE) may evolve into necrosis, fistula in the thorax, and sepsis; thus, it is also associated with high mortality.We investigated and analyzed the risk of aortic aneurysm (AA) in a cohort study of patients with PE.A total of 34,250 patients diagnosed with PE were identified as the PE cohort, and 137,000 patients without PE were selected randomly as the control group and matched by sex, age, and index year of PE diagnosis. Patients ages 20 years and younger with a history of AA were excluded. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…We found that the percentage prevalence of pre-existing comorbidity was high (median 72%) with a wide range of chronic conditions affecting the major organ systems. This is consistent with large population-based studies, which have reported comorbidity prevalence of up to 74% [5] and supports the hypothesis that the rise in the incidence of pleural infection in recent years might be associated with an increasingly ageing, multi-morbid population.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found that the percentage prevalence of pre-existing comorbidity was high (median 72%) with a wide range of chronic conditions affecting the major organ systems. This is consistent with large population-based studies, which have reported comorbidity prevalence of up to 74% [5] and supports the hypothesis that the rise in the incidence of pleural infection in recent years might be associated with an increasingly ageing, multi-morbid population.…”
Section: Discussionsupporting
confidence: 91%
“…This is supported by data from large population-based cohorts demonstrating that incidence is skewed towards older persons and is rising more quickly in this group [2, 6]. Furthermore, rates of comorbidity in pleural infection have been reported as being as high as 74% [2, 5], and patients with increased pre-existing comorbidity have higher mortality rates (20.6% if Charlton comorbidity score (CCS) >2 points, 6% if CCS 0 points) [2].…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…[1] In a previous study, empyema was associated with an increased risk of aortic aneurysm after adjusting for age, sex, and the comorbidities of diabetes, hypertension, hyperlipidemia, COPD, heart failure, coronary artery disease, stroke, bacterial endocarditis, and rheumatic endocarditis. [2] COPD can lead to the impairment of pulmonary defense and an increased risk of pneumonia. [3] Empyema is a complication of pneumonia in which pus and fluid from infected lung tissue collect in the pleural cavity, although empyema may arise from other infections as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although, all of the existing studies were based on single treatment procedure without any comparisons (i.e., surgical or nonsurgical) and hence, their results could not be reliable for choosing the best one. There are several cohort studies carried out on empyema [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] from which only two of them were retrospective [14] , [17] and they were analyzing the risk of aortic aneurysm [14] as well as the characteristics of medically and surgically treated patients in terms of chest pain, IV antibiotics, chest tube, and intrapleural fibrinolytics [17] . A retrospective cohort study is used for comparing medical treated groups for whom the information for the outcomes are recorded in a long period of time to be analyzed later in the near future [18] .…”
Section: Introductionmentioning
confidence: 99%